Factors associated with women's perception of and satisfaction with quality of intrapartum care practices in Swaziland. (February 2018) - Gamedze-Mshayisa, Dumsile Innocentia; Kuo, Su-Chen; Liu, Chieh-Yu; Lu, Yu- Ying
Abstract: Objective: giving birth is a lifetime event, where the quality of care a woman receives has the potential to affect her or her baby both physically and emotionally either on a short-term or long-term basis. This study aimed at identifying factors associated with women's perception of and satisfaction with the quality of intrapartum care as well as their future loyalty intentions in two regional hospitals in Swaziland. Methods: this is a correlational study where data were collected from 383 women conveniently selected from two regional hospitals where they gave birth. The QPP-I, SHPC, AND WOM questionnaires were used for data collection which was done from July to September 2016. Findings: the results reflected that women's satisfaction with quality of intrapartum care total mean score was (M±SD = 74.17±10.1), a perceived reality of intrapartum care practices total mean score of (M±SD = 96.94±16.0), a high subjective importance total mean score (M±SD = 117.78±10.5), and above average future loyalty intension total mean score (M±SD 1.67±0.69). Factors that significantly predicted women's satisfaction with quality of intrapartum care include, perceived quality ( F = 54.13, p <0.001 with 28% R 2 variance), demographic variables (educational level, employment status and gestational weeks) ( F = 10.66, p =<0.001, with 8% R 2 variance), future loyalty intensions ( F = 48.57, p <0.001with 7% R 2 variance), and subjective importance ( F = 44.74, p <0.001 with 1% R 2 variance). Conclusion: the study revealed that women's perceived reality of and satisfaction with the quality of intrapartum care practices was suboptimal. Improvement should be focused on evidence-based intrapartum care that is women-centered, involving the clients in decision-making and also a comprehensive childbirth education for the pregnant mothers. Highlights: Perceived reality of intrapartum care was above average. Items that were rated high for perceived quality were also rated high for subjective importance. Satisfaction with quality of intrapartum care was high. Women's future loyalty intensions was above average. There was a strong positive correlation between perceived quality, importance, satisfaction and future loyalty intensions.